Recent Developments in Corporate Governance: An Overview - Gillan, Stuart L. (Journal of Corporate Finance, 2006)
I develop a corporate governance framework, provide a broad overview of recent corporate governance research, and place each of the Special Issue papers within the context of this framework. The papers in the issue contribute to our understanding of a wide range of governance topics including: the role of antitakeover measures, board structure, capital market governance, compensation and incentives, debt and agency costs, director and officer labor markets, fraud, lawsuits, ownership structure, and regulation. In short, the papers span almost every aspect of governance systems.